ETIOLOGY AND REGIONAL VARIATION OF ORAL CANCER- A REVIEW - Ahmad, Paras; Karobari, Mohmed Isaqali; Mahmood, Rizwan; Liszen, Tang; Asif, Jawaad Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The American National Cancer Institute (National Cancer Institute, 2009), given the classification of cancer, can be classified into five primary types including central nervous system cancers, sarcomas, leukaemias, carcinomas, myelomas and lymphomas. The most common type of cancer which covers external and internal cell surfaces arising for the cell is carcinoma, i.e., mouth, lung, breast and colon. The confirmed primary known oral cancer risk factors are tobacco consumption and alcohol intake: it is believed that about 75% of head and neck cancers are associated with these habits. Other risk factors include betel quid chewing, infection with HPV, genetics, and radiation.